Dilema Hukum Dalam Pengangkatan Anak Oleh Pekerja Migran Indonesia Di Malaysia - Habibie, Dieva Ahmad; Sadjeli, Siti Soraya; Gabriella, Theresia; Rasyed, Muhammad Al; Saarah, Arini; Ramadhani, Dwi Aryanti (Jurnal EL-QANUNIY: Jurnal Ilmu-Ilmu Kesyariahan dan Pranata Sosial, 2024)
This study examines the differences in child adoption regulations between Indonesia and Malaysia, and their impact on the legal protection of children adopted by Indonesian migrant workers in Malaysia. Employing a socio-legal approach, this study analyzes the regulations in both countries as well as relevant literature on child protection and international migration. The findings reveal that discrepancies in regulations, particularly regarding adoption procedures and recognition of citizenship, result in legal uncertainties for adopted children. These children often face difficulties in obtaining birth certificates, legal identity, and access to basic rights such as education and health. This study highlights the importance of harmonizing regulations between the two countries and strengthening international cooperation to protect the rights of children adopted by migrant workers. The practical implications of this research include the need for more comprehensive policies to protect cross-border children and to raise public awareness of the importance of child protection.